Dependence of electrical performance on structural organization in polymer field effect transistors. Issue 14 (16th April 2017) - Bittle, Emily G.; Ro, Hyun Wook; Snyder, Chad R.; Engmann, Sebastian; Kline, R. Joseph; Zhang, Xinran; Jurchescu, Oana D.; DeLongchamp, Dean M.; Gundlach, David J.
ABSTRACT: Organic semiconductors (OSCs) are strong contenders for use in printed, flexible electronics. Although organic electronic materials have been studied for many years, the physics of charge transport is still under investigation. This is in part due to variability resulting from the large variety of molecules that can be synthesized and inconsistency in electrical characterization due to device and processing conditions. Molecular ordering in OSCs is known to alter the charge transport characteristics and attention to long range and short range ordering provides clues as to the nature of transport pathways. Here, we study ordered regioregular poly(3‐hexylthiophene‐2, 5‐diyl) films carefully prepared to obtain a set of three samples with incrementally increasing order on identical transistor architectures. Ordering was characterized using a variety of short and long range techniques to probe the coherence and number of crystallites formed during processing, and the correlation between these different measures of order are quantified. We observe three changes in transistor behavior that show a shift from non‐ideal to more textbook‐like characteristics with increasing order: reduction of the contact resistance, shift to field‐independent mobility, and a shift from a diode‐like (S‐shaped) to linear response at low lateral fields. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1063–1074 Abstract : The impact of order in semiconducting polymers on the charge transport of organic transistors is studied by systematically controlling the crystallization of poly(3‐hexylthiophene 2, 5‐diyl) (P3HT). Quantitative measurements of order by X‐ray, optical, and calorimetric methods are compared. Increasing order results in improved electrical performance with a decrease in abnormalities in IV characteristics, decreased contact resistance, and a crossover to field‐independent mobility.